Green Energy Consumption and Inclusive Growth: A Comprehensive Analysis of Multi-Country Study - Ghouse, Ghulam; Aslam, Aribah; Bhatti, Muhammad Ishaq (Frontiers in Energy Research, 2022)
Whenever there is a question of environmental quality and inclusive economic growth, green and renewable energy consumption leads the debate. This paper explores the relationship between green energy consumption and inclusive economic growth. It employs GMM panel data modelling frameworks for understanding the “green energy vis-à-vis -growth paradox”. It uses post-COVID-19 data for eighty-three countries between 2010 and 2020. These countries are divided into high-, middle- and low-income as per the World Bank’s classifications. The selected composite variables are consisting of GDP growth, poverty, income equality and employment measures. The study reports that green energy positively contributes to inclusive growth despite its lower contribution to overall energy usage in low-income countries. It observes that socio-digital inclusion and green energy together impact positively on inclusive growth in all income groups (low, middle and high). This means citizens of the selected countries are aware of the pros and cons of green energy that helps countries to mitigate the negative impacts of countries’ transition to clean energy usage in terms of job losses, higher costs of clean energy and uncertainty to energy supply. Furthermore, results also reveal that green energy is significant contributor towards achieving inclusive growth, however it his highly significant in high income countries compared to other groups, showing its higher use in it. This comprehensive study is the first of its kind providing comparative analysis of 83 countries which explores and compares the interesting impacts of green energy consumption on inclusive growth in global data from the designated income groups.